Role of Fused Mycobacterium tuberculosis Immunogens and Adjuvants in Modern Tuberculosis Vaccines - Junqueira-Kipnis, Ana Paula; Marques Neto, Lázaro Moreira; Kipnis, André (Frontiers in Immunology, 2014)
Several approaches have been developed to improve or replace the only available vaccine for tuberculosis (TB), BCG (Bacille Calmette Guerin). The development of subunit protein vaccines is a promising strategy because it combines specificity and safety. In addition, subunit protein vaccines can be designed to have selected immune epitopes associated with immunomodulating components to drive the appropriate immune response. However, the limited antigens present in subunit vaccines reduce their capacity to stimulate a complete immune response compared with vaccines composed of live attenuated or killed microorganisms. This deficiency can be compensated by the incorporation of adjuvants in the vaccine formulation. The fusion of adjuvants with Mycobacterium tuberculosis (Mtb) proteins or immune epitopes has the potential to become the new frontier in the TB vaccine development field. Researchers have addressed this approach by fusing the immune epitopes of their vaccines with molecules such as interleukins, lipids, lipoproteins, and immune stimulatory peptides, which have the potential to enhance the immune response. The fused molecules are being tested as subunit vaccines alone or within live attenuated vector contexts. Therefore, the objectives of this review are to discuss the association of Mtb fusion proteins with adjuvants; Mtb immunogens fused with adjuvants; and cytokine fusion with Mtb proteins and live recombinant vectors expressing cytokines. The incorporation of adjuvant molecules in a vaccine can be complex, and developing a stable fusion with proteins is a challenging task. Overall, the fusion of adjuvants with Mtb epitopes, despite the limited number of studies, is a promising field in vaccine development.